Perspectives for Development of Hydrotechnical Infrastructure in Poland in view of the European Union Water Policy - Walczykiewicz, Tomasz (Problemy Ekorozwoju, 2014)
The article presents general conditions and perspectives for development of hydrotechnical infrastructure in Poland, as compared to the European Union water policy, which take into account demands of sustainable development. The hydrotechnical infrastructure analyzed in the article includes technical projects associated with flood control, water power engineering and water transport. Poland is in a particular situation because, due to historical determinants, including partition of its territory and war damages, the development of water management processes which may be observed in western European countries proceeded at a slower pace or simply did not take place at all. The current water policy stemming from the Water Framework Directive should be based on harmonization of economic growth and environmental requirements. In addition, cohesive sectoral planning documents are required. It is also imperative that water management plans for river basins take priority over other water management plans.